2015
DOI: 10.1021/acs.langmuir.5b00630
|View full text |Cite
|
Sign up to set email alerts
|

Non-aqueous Isorefractive Pickering Emulsions

Abstract: Non-aqueous Pickering emulsions of 16–240 μm diameter have been prepared using diblock copolymer worms with ethylene glycol as the droplet phase and an n-alkane as the continuous phase. Initial studies using n-dodecane resulted in stable emulsions that were significantly less turbid than conventional water-in-oil emulsions. This is attributed to the rather similar refractive indices of the latter two phases. By utilizing n-tetradecane as an alternative oil that almost precisely matches the refractive index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
1
46
1
Order By: Relevance
“…Finally, Thompson et al just reported the preparation of non-aqueous Pickering emulsions [111]. In this case the water phase is replaced with ethylene glycol, which is immiscible with a wide range of n-alkanes.…”
Section: Raft Dispersion Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Thompson et al just reported the preparation of non-aqueous Pickering emulsions [111]. In this case the water phase is replaced with ethylene glycol, which is immiscible with a wide range of n-alkanes.…”
Section: Raft Dispersion Polymerizationmentioning
confidence: 99%
“…Interestingly, judicious selection of an appropriate n-alkane with approximately the same refractive index as that of ethylene glycol enables the production of near-isorefractive emulsions. More specifically, emulsification of ethylene glycol (EG) with n-tetradecane using L 16 -B 37 worms dispersed in n-tetradecane produces almost transparent EG-in-n-tetradecane Pickering emulsions that exhibited up to 81% transmittance across the visible spectrum [111].…”
Section: Raft Dispersion Polymerizationmentioning
confidence: 99%
“…39,40 It has been proposed that the transparency induced by compressed gases is related to the insertion of gas molecules into the interfacial lm, resulting in a change in the curvature and creating smaller droplets. 36 The transparent emulsion formed via CO 2 pressurization of TX-100 (poly(oxyethylene)iso-octylphenyl ether)/water/ isooctane at P T ¼ 3.90 MPa was characterized by small-angle Xray scattering (SAXS), yielding spherical droplets of diameter 92 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In a heterogeneous reaction system, the absorbed flux quantities depend on (vide supra) and the diminution of radiation due to forward-and back-scattering. The monochromatic incident photon flux 0 ( , ) at any point of an irradiated heterogeneous system may be calculated in applying the radiative transfer equation (RTE) [48,49] leading to…”
Section: Radiation Penetration and Distributionmentioning
confidence: 99%